Restoring harm: a psychosocial approach to victims and restorative justice - Bolívar, Daniela (Routledge frontiers of criminal justice, 2019)
Prologue: from satisfaction to restoration: a mixed-method and quasi-experimental study -- Victims, restoration, and restorative justice: findings, debates and gaps -- Victims' perspectives on harm and restoration -- The phenomenon of victim participation in restorative justice -- Restoring victims: the role of victim-offender mediation -- Towards a psycho-social model of restorative justice -- Epilogue: the challenge of a victim-sensitive restorative justice practice.